Growth and Progress - Jeri W Dunkin (Online Journal of Rural Nursing and Health Care, 2012)
Growth and progress: Both words describe development and evolution of a being or thing. And both are very appropriate for the Online Journal of Rural Nursing and Health Care as we bring to close our tenth year of online publication. Growth: The readership of the Journal has increase dramatically. This is especially true of the last five years. In 2005 there were 63,010 hits on the Journal and in the first 10 months of 2009 there were over 12 times that number (7,984,640). That is quite an increase! In examining the data I found that about 65% of the readers are in the United States but the other 35% come from over 90 countries. The articles submitted for review for the journal are also indicative of substantial growth, with only an occasional submission from countries outside the United States to almost a third of the submissions in 2009 coming from authors in other countries. The Editorial Board and Review panel also have members from around the world. In addition the breadth of topics has grown as well. In this spirit of growth this issue has two guest Editorials. They are on very different topics and I hope hold interest for our readers. In addition, this issue has more articles included than ever before. It is very exciting to see the response to, and the need for the Online Journal of Rural Nursing and Health Care. Progress: At the same time we have made changes occasionally to facilitate the publication as we have progressed through the evolution of the Journal. Another change will be coming in 2010 as we take the Online Journal of Rural Nursing and Health Care out of the open publication format and put it into the Subscription Based Journal category and move its publication to an established publisher rather than a voluntary process for the Editor and Managing Editor. Our promise to you is that we will do our best to keep it as accessible as possible for all our readers.